New findings on the effect of glyphosate on autotrophic and heterotrophic picoplankton structure: A microcosm approach - Sabio y García, Carmen Alejandra (2020)
Massive use of glyphosate-based herbicides in agricultural activities has led to the appearance of this herbicide in freshwater systems, which represents a potential threat to these systems and their communities. These herbicides can affect autotrophic and heterotrophic picoplankton abundance. However, little is known about glyphosate impact on the whole structure of these assemblages. Herein, we used an 8-day long microcosm approach under indoor controlled conditions to analyze changes in the structure of picoplankton exposed to a single pulse of glyphosate. The analyzed picoplankton correspond to two outdoor ponds with contrasting states: “clear” (chlorophyll-a = 3.48 μg L−1± 1.15; nephelometric turbidity, NTU = 1) and “turbid” (chlorophyll-a = 105.96 μg L−1 ± 15.3; NTU = 48). We evaluated herbicide impact on different picoplankton cytometric populations and further explored changes in bacterial dominant operational taxonomic units (OTUs) fingerprinting. We observed that glyphosate induced a drastic decrease in the abundance of phycocyanin-rich picocyanobacteria. Particularly, in the turbid system this effect resulted in an 85 % decrease in the abundance of the whole autotrophic picoplankton. Glyphosate also changed the structure of the heterotrophic fraction by means of changing bacterial dominant OTUs fingerprinting patterns in both systems and by shifting the relative abundances of cytometric groups in the clear scenario. These results demonstrate that upon glyphosate exposure picoplanktonic fractions face not only the already reported changes in abundance, but also alterations in the composition of cytometric groups and of bacterial dominant operational taxonomic units. This research provides suitable and still little explored tools to analyze agrochemical effects on picoplanktonic communities.